2018
DOI: 10.1007/s10555-018-9733-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional link between plasma membrane spatiotemporal dynamics, cancer biology, and dietary membrane-altering agents

Abstract: The cell plasma membrane serves as a nexus integrating extra- and intracellular components, which together enable many of the fundamental cellular signaling processes that sustain life. In order to perform this key function, plasma membrane components assemble into well-defined domains exhibiting distinct biochemical and biophysical properties that modulate various signaling events. Dysregulation of these highly dynamic membrane domains can promote oncogenic signaling. Recently, it has been demonstrated that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 377 publications
2
41
0
1
Order By: Relevance
“…Basic research has shown that increased cholesterol is a metabolic signature in breast cancer and its accumulation is positively correlated with advanced clinical staging and metastasis. [5,55,56] Cholesterol promotes breast cancer via several mechanisms, involving an interplay among modified lipoproteins, proinflammatory signaling pathways, and breast cancer tumorigenic processes. However so far, the connection between cholesterol content and the physical properties of breast cancer cells are poorly understood mainly due to the lack of appropriate techniques enabling to study the PM-associated cholesterol content and mechanics of breast cancer cell directly on living cells.…”
Section: Discussionmentioning
confidence: 99%
“…Basic research has shown that increased cholesterol is a metabolic signature in breast cancer and its accumulation is positively correlated with advanced clinical staging and metastasis. [5,55,56] Cholesterol promotes breast cancer via several mechanisms, involving an interplay among modified lipoproteins, proinflammatory signaling pathways, and breast cancer tumorigenic processes. However so far, the connection between cholesterol content and the physical properties of breast cancer cells are poorly understood mainly due to the lack of appropriate techniques enabling to study the PM-associated cholesterol content and mechanics of breast cancer cell directly on living cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated in the literature that there is a direct connection between the fluidity of the membrane and the rising of different illnesses [ 5 , 6 , 7 , 8 , 9 ]. In particular, increased levels of cholesterol decrease the membrane fluidity and alter the spatial organization of membrane nano- and micro-domains and nourish the hypothesis around the existence of so-called lipid rafts [ 10 , 11 ]. The presence of different domains in membranes manifests itself through their changing softness, and is a direct result of varying degrees of fluidity; this heterogeneity may be of interest in the dissemination of metastatic tumors [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The attenuation of oncogenic protein activity by modulating the membrane organization of essential proteins and lipids was proven and this is a promising way to use such an approach to manage cancer expansion. It is worth underlining that omega-3 has a very potent influence on membrane organization and this ability, combined with the anti-inflammatory activity, should be developed toward successful cancer treatments [ 171 , 172 ]. However, it is also evident that, without assessing the membrane status in the individual, the assignment of the lipid strategy cannot be precise, in types and doses, thus even bringing about contrasting clinical outcomes since the membrane unbalance results or remains altered.…”
Section: Some Considerations Of Fatty Acid-based Membrane Lipidomimentioning
confidence: 99%